Side Effects as Determinants of Contraceptive Non-Compliance and Failure among Fertile Age Couples in Makassar, Indonesia - Andi Masnilawati; Fatma Jama; Nia Karuniawati; Nurul Ramadani (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2026)
Contraceptive side effects are a key determinant of contraceptive choice and continuation and often lead to discontinuation or method switching. This poses a public health concern as it reduces contraceptive adherence and effectiveness, thereby increasing the risk of unintended pregnancy, unintended birth, and abortion. This study aimed to examine the association between contraceptive side effects, non-compliance, and contraceptive failure among fertile-age couples in the working area of the Kassi Community Health Center, Makassar City. An observational analytical study with a cross-sectional design was conducted among 76 active family planning acceptors, selected using purposive sampling. Data were collected through structured interviews using questionnaires. The results showed that menstrual disorders (p = 0.004), vaginal discharge (p = 0.002), weight changes (p = 0.041), mood changes (p = 0.012), and decreased libido (p = 0.002) were significantly associated with non-compliance. Menstrual disorders (p = 0.006), vaginal discharge (p = 0.003), and decreased libido (p = 0.015) were also significantly associated with contraceptive failure. In addition, non-compliance was strongly associated with contraceptive failure (p = 0.000). Contraceptive side effects contribute both directly and indirectly to contraceptive failure, primarily through non-compliance, particularly among users of hormonal contraception. Strengthening family planning counseling and providing comprehensive information on contraceptive effectiveness and side effects are essential to reduce non-compliance and failure rates.